Development of alternating current circuit simulation as essential learning support for senior high school student - Mayang Dwinta Trisniarti; Pujayanto Pujayanto (International Journal of Science and Applied Science: Conference Series, 2017)
In this study an interactive simulation of Alternating Current circuit was developed by using Articulate Storyline 2 and Adobe Flash CS 6 programs. The aim of this study was providing a computer interactive simulation as essential learning support for Senior High School student. One of the most important features of AC circuit simulation is the easily and continuous material to attain learning objectivity and interest toward students. This AC circuit simulation is built to create real-time sine wave graphs so that student could compare the result if the variable were changed gradually. The validation is held through several experts and reviewers due to get obtained through questionnaires. The results of this research could be concluded that AC circuit simulation for Senior High School Physics have good criteria based on user interface, i.e. 50% of respondents rated enough, 16.67% of respondents rated good, and 33.33% of respondents rated very good. Based on maintenance, i.e. 50% of respondents rated enough, 20% of respondents rated good, and 30% of respondents rated very good. Then based on usability, i.e. 6.67% of respondents rated good and 93.33% rated very good. Furthermore, based on understanding, i.e. 6.67% of respondents rated enough, 30% of respondents rated good, and 73.33% of respondents rated very good. The use of AC circuit simulation could improve the senior high school students’ cognitive ability on the Physics’s course, i.e. with the average score increased from 68.67 to 80.5 based on 30 students.